2014
DOI: 10.1016/j.arthro.2014.02.036
|View full text |Cite
|
Sign up to set email alerts
|

Results From the Swedish National Anterior Cruciate Ligament Register

Abstract: Purpose: The purpose of the study was to report baseline variables and clinical outcome for almost 24,000 patients entered into the Swedish national ACL register. Methods:The register consists of two parts; one section in which surgeons report baseline and surgical data and one section in which patients report the Knee injury and Osteoarthritis Outcome Score (KOOS) and the EQ-5D before and one, two and five years after surgery.Results: By December 2012, 23,744 patients had been entered in the surgeons' part of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
183
2
12

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 213 publications
(207 citation statements)
references
References 27 publications
10
183
2
12
Order By: Relevance
“…The study population was identified through the Swedish national ACL register, which captures >90% of all ACLRs in the country, 22 and via advertisement on the websites of three regional soccer districts near the university (to facilitate testing …”
Section: Participantsmentioning
confidence: 99%
“…The study population was identified through the Swedish national ACL register, which captures >90% of all ACLRs in the country, 22 and via advertisement on the websites of three regional soccer districts near the university (to facilitate testing …”
Section: Participantsmentioning
confidence: 99%
“…A range of demographic factors have also been related to worse health-related QOL outcomes within five years of ACLR, these include being a current or previous tobacco smoker (Dunn et al, 2015;Kvist, Kartus, Karlsson, & Forssblad, 2014) having an older age, an increased BMI or having had fewer years of education at the time of ACLR (Dunn et al, 2015). Reporting lower pre-operative knee-related and health-related QOL scores has been associated with reporting lower scores on the same measures postoperatively (Bryant, Stratford, Marx, Walter, & Guyatt, 2008;Dunn et al, 2015).…”
Section: Quality Of Life Within Five Years Of Anterior Cruciate Ligammentioning
confidence: 99%
“…With delayed ACLR, a significant increase in the number of meniscus and cartilages injuries is observed [61,104]. In Scandinavia, the median time from injury-to-surgery ranged from 7-10 months [72] (median 8 months in Sweden [114]). In the US, the median time was 2.4 months [126].…”
Section: Reconstructionmentioning
confidence: 99%
“…The incidence increases severalfold in sports, and is as high as 500-8500/100 000 participants/year in football [221], the main sport in Sweden. The most common sport for both females and males performed at ACL injury and who later undergo ACLR in Sweden is football (36% vs. 49%), and after that alpine skiing (18% vs. 10%), handball (9% vs. 3%) and floorball (8% vs. 10%) [114]. The female-to-male ACL injury rate is different depending on sport.…”
Section: Epidemiology and Aetiology Of A Primary Acl Injurymentioning
confidence: 99%
See 1 more Smart Citation